1984
DOI: 10.1159/000275704
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Labyrinthine Fistula in Cholesteatoma Surgery

Abstract: The presence of a labyrinthine fistula has remained one of the major problems in cholesteatoma surgery. Confronted with this problem, the surgeon may ultimately base his choice of procedure on four basic conditions: the size of the fistula, its location in the ear, the condition of the other ear, and the cochlear function. Our attitude has been changing, and currently we prefer to perform a staged closed tympanoplasty. When a closed technique is performed, we either remove the cholesteatoma matrix and then cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 10 publications
2
41
0
Order By: Relevance
“…Fistulas occur almost exclusively in the setting of a cholesteatoma. 2 ' 47 In the current study, a cholesteatoma was found in 33 of the 34 cases (97%). The lateral SCC was the most common site involved in this study (94%) and in previously reported cases.…”
Section: Discussionsupporting
confidence: 44%
“…Fistulas occur almost exclusively in the setting of a cholesteatoma. 2 ' 47 In the current study, a cholesteatoma was found in 33 of the 34 cases (97%). The lateral SCC was the most common site involved in this study (94%) and in previously reported cases.…”
Section: Discussionsupporting
confidence: 44%
“…Some authors classify the Wstulas according to their size in mm [23,26]. Others believe that depth of invasion better correlates with prognosis than size [27].…”
Section: Classiwcation Of Labyrinthine Wstulamentioning
confidence: 99%
“…Fistula of the labyrinth complicating chronic suppurative otitis media (CSOM) has been reported in 5-13% of patients who underwent mastoidectomy for cholestatoma (1)(2)(3)(4)(5)(6)(7). Bone erosion and subsequent stula formation most frequently occurs in the horizontal semicircular canal in adults with a long history of CSOM (2,8,9), but stulas have also been reported in younger patients with a shorter duration of CSOM (2).…”
Section: Introductionmentioning
confidence: 99%